Costs of abduction treatment in developmental dysplasia of the hip. Analysis of 900 patients - Vilma Lankinen; Riikka-Liisa Vuorinen; Mika Helminen; Karim Bakti; Jarmo Välipakka; Hannele Laivuori; Anna Hyvärinen (Annals of Medicine, 2023)
AbstractBackground Developmental dysplasia of the hip (DDH) is a disorder of hip development that leads to dysplasia, subluxation, or total hip dislocation. Early detection of DDH is important, and early initiation of abduction treatment is key to successful correction of the hip joint. However, mild forms of DDH, including hip instability without complete dislocation, have good spontaneous healing potential, and a watchful waiting strategy in mild DDH has been found to be safe. In this study, we aimed to evaluate the cost differences between different treatment strategies for DDH.Material and methods Data were collected retrospectively from the medical records of all children diagnosed with diagnosis and treatment of DDH in Tampere University hospital between 1998 and 2018. In total, 948 patients were included in the study. Patients who underwent casting or operative treatment (n = 48) were excluded from the analysis. All Ortolani positive children were subjected to early abduction treatment. Children with Ortolani negative DDH were subjected to either watchful waiting or early abduction treatment, based on the clinicians’ decision. The regression model estimates for the number of clinical visits with and without ultrasound examination were assessed together with cost reports from Tampere University Hospital for the calculation of savings per patient in spontaneous recovery.Results Alpha angles at one month of age (p < 0.001) and treatment method (p < 0.001) affected the number of clinical visits and ultrasound examinations during the treatment follow-up. A low alpha angle predicted closer follow-up, and children with spontaneous recovery had lower numbers of clinical visits and ultrasound examinations than children in abduction treatment. Spontaneous recovery was found to result in approximately 375€/patient savings compared to successful abduction treatment.Conclusion With correct patient selection, a watchful waiting strategy is cost-effective in treating mild developmental dysplasia of the hip, considering the high percentage of spontaneous recovery.